High Quality ATAC-Seq Data Recovered from Cryopreserved Breast Cell Lines and Tissue - Fujiwara, Saori (Sci Rep, 2019)
DNA accessibility to transcription regulators varies between cells and modulates gene expression patterns. Several “open” chromatin profiling methods that provide valuable insight into the activity of these regulatory regions have been developed. However, their application to clinical samples has been limited despite the discovery that the Analysis of Transposase-Accessible Chromatin followed by sequencing (ATAC-seq) method can be performed using fewer cells than other techniques. Obtaining fresh rather than stored samples and a lack of adequate optimization and quality controls are major barriers to ATAC’s clinical implementation. Here, we describe an optimized ATAC protocol in which we varied nuclear preparation conditions and transposase concentrations and applied rigorous quality control measures before testing fresh, flash frozen, and cryopreserved breast cells and tissue. We obtained high quality data from small cell number. Furthermore, the genomic distribution of sequencing reads, their enrichment at transcription start sites, and transcription factor footprint analyses were similar between cryopreserved and fresh samples. This updated method is applicable to clinical samples, including cells from fine needle aspiration and tissues obtained via core needle biopsy or surgery. Chromatin accessibility analysis using patient samples will greatly expand the range of translational research and personalized medicine by identification of clinically-relevant epigenetic features.